Early white matter involvement in an infant carrying a novel mutation in ACOX1. (May 2016) - Masson, R.; Guerra, S.; Cerini, R.; Pensato, V.; Gellera, C.; Taroni, F.; Simonati, A.
Abstract: We describe the clinical findings and MRI features observed in a child who presented a two-step disease course: he was hypotonic at birth and soon afterwards developed seizures, which were partially responsive to treatment; he subsequently showed developmental delay and a progressive neurological deterioration with the onset of severe seizures at around three years of age. Head MRI at age 20 days was unremarkable, whereas at 25 months it showed bilateral hyperintensity of the deep cerebellar nuclei; five months later, the signal hyperintensity was also present in the cerebellar white matter and ventral pontine fibre tracts. Molecular analysis revealed a novel ACOX1 mutation, predicting a largely truncated protein. The white matter involvement, which followed an ascending trajectory from cerebellar and brainstem structures to the cerebral hemispheres, seemed to originate from the perinuclear white matter of the deep cerebellar nuclei.